Horse handlers’ knowledge, attitudes, and perceptions of African horse sickness in South-West, Nigeria - Olumide Odunayo Akinniyi; Taiwo Rianat Lawal; Nurudeen Rufai; Kelvin Olutimilehin Jolayemi; Joyce Amaje (Scientific Reports)
Abstract African horse sickness (AHS) is endemic in Nigeria. Despite this, little is known about the perspective of horse handlers in Nigeria regarding AHS. The study aimed to evaluate the knowledge, attitudes, and perceptions (KAP) of horse handlers in Southwest Nigeria regarding AHS. A cross-sectional survey study was conducted, which involved convenient sampling of 131 horse handlers in Lagos and Oyo States by February – April 2024. The pre-validated questionnaires were administered via face-to-face interviews, covering demographics, knowledge of AHS transmission, clinical signs, prevention and control measures, attitudes towards severity and preventability, and perceptions of AHS risk and impact. Numeric scoring categorized KAP levels as satisfactory or unsatisfactory. Data analysis used descriptive statistics, chi-square tests, and multivariate logistic regression. Result showed majority were early adults aged 20–39 years (63.4%, n = 83), highest level of education was secondary school (47.3%, n = 62), and most had more than 4 years of experience handling horses (83.2%, n = 109). Higher knowledge levels were associated with being from Lagos State (AOR = 851.4, 95% CI = 39.8-18215.2, p = 0.00), having more experience (AOR = 50.0, 95% CI = 2.7-925.9, p = 0.00), and owning larger herds (AOR = 31.6, 95%CI = 3.1-327.5, p = 0.00). Satisfactory attitudes and perceptions towards AHS prevention and control was exhibited by 98.5%. While knowledge gaps exist, the positive attitudes and perceptions present opportunities for enhancing AHS awareness and control strategies among this population of horse handlers. Future research should focus on developing and evaluating targeted interventions to address the identified knowledge gaps and maintain the positive attitudes and perceptions observed in this study.